Analysis of the information theoretically secret key agreement by public discussion. Issue 15 (23rd January 2015) - Wang, Qiuhua; Wang, Xiaojun; Lv, Qiuyun; Ye, Xueyi; Luo, Yi; You, Lin
Abstract Generally, the information theoretically secret key agreement by public discussion consists of three phases, namely, advantage distillation, information reconciliation, and privacy amplification. In the existing literatures, these three phases are studied separately, and no comprehensive consideration has been given. In this paper, we analyze the restrictive relationship among these three phases from an overall point of view. For the satellite scenario, we analyze in detail the Winnow protocol for the first time. We also present the mutual restrictive relationship between the parameters of the advantage distillation phase and the information reconciliation phase. We further address how to set the parameters of the advantage distillation and the information reconciliation to maximize the total secret key agreement efficiency. Moreover, we determine the required length range of the initial random key string to guarantee the validation of the secret key agreement. Copyright © 2015 John Wiley & Sons, Ltd.